2016
DOI: 10.1590/1809-4430-eng.agric.v36n1p46-54/2016
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse crisphead lettuce grown with mulching and under different soil water tensions

Abstract: ABSTRACT:Proper irrigation management is important both to enable adequate water supply and to minimize problems with diseases, nutrient leaching and unnecessary water and power wastes. Thus, this study aimed at improving irrigation management in greenhouses. For that reason, we assessed the effect of various water tensions on yield performance of crisphead lettuce, Raider-Plus cv., grown with mulching. KEYWORDS:Lactuta sativa, irrigation management, protected environment, soil covering. PRODUÇÃO DE ALFACE-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
5
5
0
1
Order By: Relevance
“…Bandeira et al (2011) reported that this can be explained by the decrease in leaf water potential, stomatal conductance and CO 2 flow, resulting in an adverse impact on accumulations of photoassimilate compounds and as a consequence, reduction in crop production. Water deficit effect causes changes in stomatal responses, osmotic adjustment and important movement of photoassimilates to the roots, metabolic energy consumption and affects crop production anywhere in the plant as well as its commercial quality (Geisenhoff et al, 2016). According to Soares (2007), plants submitted to increasing salinity were less tender, showing more coriaceous leaves: these characteristics were also observed in this study.…”
Section: Resultssupporting
confidence: 73%
“…Bandeira et al (2011) reported that this can be explained by the decrease in leaf water potential, stomatal conductance and CO 2 flow, resulting in an adverse impact on accumulations of photoassimilate compounds and as a consequence, reduction in crop production. Water deficit effect causes changes in stomatal responses, osmotic adjustment and important movement of photoassimilates to the roots, metabolic energy consumption and affects crop production anywhere in the plant as well as its commercial quality (Geisenhoff et al, 2016). According to Soares (2007), plants submitted to increasing salinity were less tender, showing more coriaceous leaves: these characteristics were also observed in this study.…”
Section: Resultssupporting
confidence: 73%
“…The treatment with 12 kPa favored the use of nitrogen fertilization by jambu plants, which responded with maximum productivity at the highest dose. The treatment with soil-water stress of 12 kPa maintained the soil close to field capacity, demonstrating behavior similar to the results found by Geisenhoff et al (2016) with lettuce and Lima Junior et al (2012) with carrots, who performed irrigation management based on the soil and obtained maximum productivity at stresses close to field capacity. Jambu production is benefited by the stress that maintains soil moisture close to field capacity.…”
Section: Resultssupporting
confidence: 81%
“…Water depths applied before and after treatment differentiation, as well as precipitations during the experimental period, total water supplied to the crop until harvest, number of irrigations, mean irrigation frequency, and daily water demand during treatment differentiation are shown in Table 2. The data in Table 3 showed a linear behavior in relation to water consumption per treatment, similar to that observed by Geisenhoff et al (2016) in an experiment with drip-irrigated lettuce with different stresses, in which the total applied depth decreased as the soil-water stress increased.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, an adequate irrigation allows a vigorous growth of the plant, causing less susceptibility to the attack of pathogens. With the object of finding optimal water blade and satisfactory overall production, Geisenhoff et al (2016) evaluated the crisphead lettuce yield subjected to different water tensions in the soil. Regarding the results, they reached maximum productivity in the tension of 12 kPa.…”
Section: Introductionmentioning
confidence: 99%